The little book of big management theories ... and how to use them - McGrath, James, 1952-; Bates, Bob, 1951- (Harlow, England ; New York : Pearson Education, 2017)
101 management theories from the world's best management thinkers - the fast, focussed and express route to success. As a busy manager, you need solutions to everyday work problems fast. The Little Book of Big Management Theories gives you access to the very best theories and models that every manager should know and be able to use. Cutting through the waffle and hype, McGrath and Bates concentrate on the theories that really matter to managers day-to-day. Each theory is covered in two pages - telling you what it is, how to use it and the questions you should be asking - so you can immediately apply your new knowledge in the real world. The Little Book of Big Management Theories will ensure you can: Quickly resolve a wide range of practical management problems Be a better, more decisive manager who gets the job done Better motivate and influence your staff, colleagues and stakeholders Improve your standing and demonstrate that you are ready for promotion All you need to know and how to apply it - in a nutshell.
Keywords: Management; Employee motivation; Organizational change